Zamyšlení nad jedním stabilizačním programem (Czech Journal of International Relations, 1992)
Ners K., van Houwelinger A., Palmer M., Steel K. S.: „Moving Beyond Assistance“. Final Report of the IEWS Task Force on Western Assistance to Transition in the Czech and Slovak Republik, Hungary and Poland. Institute for East-West Studies, European Studies Center , New York, Prague, Štiřín, Warszaw, 1992, 80 stran.